Systematic review of cattle responses to viral and bacterial bovine respiratory disease pathogens and effect of high ambient temperaure on viral replication and serology to an intranasal modified-live (bovine rhinotracheitis-parainfluenza-3) viral vaccine in beef cattle - Grissett, Gretchen Phoebe (Kansas State University, 2014)
Objective- To compare serologic response and viral replication following intranasal administration of a modified-live bovine rhinotracheitis (IBR) parainfluenza-3 (PI-3) vaccine in high (32°C) and moderate (21°C) ambient temperatures. Animals- 28 heifers (mean body weight, 206.8 kg) Procedures- Heifers randomly allocated to treatment groups: High Ambient Temperature (HAT, n=10): received vaccine, housed outdoors, Moderate Ambient Temperature (MAT, n=10): received vaccine, housed indoors, High Ambient Control (HAC, n=4): no vaccine, housed outdoors, Moderate Ambient Control (MAC, n=4): no vaccine, housed indoors. Rectal and nasal mucosal temperatures were recorded every 2 hours from 8am to 8pm on trial days 0 and 1. Nasal swabs were collected on trial days 0 through 7 for virus isolation. Serum samples were collected for serology on trial days 0, 7, 14, and 28. Results- Rectal temperatures did not differ among treatment groups over the study period, but nasal temperatures were higher in the HAT calves compared to MAT group at study hours: 6, 24, 30, 32, and 38. Two weeks post-vaccination, IBR titers were significantly greater in vaccinates (HAT,MAT) relative to non-vaccinates (HAC, LAC), but no differences were identified among HAT and MAT. Viable IBR virus was recovered via virus isolation from all vaccinated calves (HAT,MAT) on trial days 1 through 6. Conclusions and Clinical Relevance- The ability to isolate IBR and stimulate the calf immune response following administration of a modified-live IBR-PI3 intranasal vaccine did not differ in calves housed in temperature-controlled and high ambient temperature environments.
Keywords: Bovine respiratory disease; Infectious bovine rhinotracheitis; Parainfluenza-3; Intranasal vaccine; Virus shedding; Heat stress; Agriculture, General (0473); Immunology (0982); Veterinary Medicine (0778)